RESTORING ELECTRICITY USE WITH THE SPOLIATION REMEDY: A CRITICAL COMMENT ON ESKOM HOLDINGS SOC LTD V MASINDA (The Pretoria Student Law Review, 2021)
In Eskom Holdings SOC Ltd v Masinda1 (‘Masinda’) teams from the appellant removed various illegal connections to the national electricity reticulation grid. The removal was animated by a concern for the well-being of those people living in homes with illegal connections and to prevent damage to their property as a result of these dangerous connections.2 While the exact reasons for the removal of the illegal connections were not clearly articulated in the appellant’s submissions, it appears that the connections constituted an immediate danger to the public because the equipment were too small; it did not meet the prescribed quality standards; and it was not installed by an authorised contractor.3 The respondent argued that she used the electricity in her home by drawing supply through a prepaid meter and that this supply constituted an incident of her occupation. She successfully sought the restoration ante omnia of the electricity supply to her home in the Eastern Cape Division of the High Court, Mtatha.4 On appeal Leach JA reasoned that it could not have been the intention of the court a quo to order the restoration ante omnia of a connection ‘that was unlawful and a danger to the public.’ Restoration ante omnia that ‘complied with the necessary requirements of safety’ would not only have required the appellant to do something more than restoring the property to its former state,5 but also extended the purpose of the spoliation remedy to include the ‘reconstituted equivalent’6 of the specified property.7 However, if the court a quo intended the restoration ante omnia of an unlawful and dangerous electricity supply,8 the further difficulty would be that the order would be directing the appellant to ‘commit an illegality’ which itself would be sufficient for a court to refuse the spoliation remedy.9 Finally, Leach JA reasoned that the mere existence of an electricity reticulation supply in the respondent’s home is insufficient to afford her a right that qualified as an incident of her occupation.10 He therefore upheld the appeal11 and dismissed the respondents ‘terse’ claim as ‘misplaced’ and ‘insufficient’.12 In this article I provide a critical comment on the Masinda judgment. I seek to do so by providing a brief exposition of the importance of having access to and being able to stop unlawful interfere with your access to electricity in part 2. In part 3 I set out the requirements, features and application of the mandament van spolie. This is followed in part 4 with an analysis of the growing jurisprudence (comprising two high court judgments that predate democracy and two judgments from the Supreme Court of Appeal in the past decade) where the mandament van spolie was used to seek restoration ante omnia of electricity use.
Keywords: Eskom Holdings SOC Ltd v Masinda; illegal connections; national electricity reticulation grid; spoliation remedy